Short Communication: Investigating gonad length and fecundity in mudskippers (Gobiidae) at the Musi River estuary, South Sumatra, Indonesia - Moh Rasyid Ridho; Enggar Patriono; Dina Rahmawati; RAHMAT PRATAMA; MUHAMMAD AVESENA (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ridho MR, Patriono E, Wati DR, Pratama R, Avesena M. 2021. Short Communication: Investigating gonad length and fecundity in mudskippers (Gobiidae) at the Musi River estuary, South Sumatra, Indonesia. Biodiversitas 22: 4413-4420. Information on the biological aspects of mudskipper (Gobiidae) reproduction is needed as a conservation effort to use economically valuable and sustainable resources in the future. This can be used to enrich the information on the status of the mudskipper research at the Musi River estuary, South Sumatra, Indonesia. The field sampling was carried out by using the purposive sampling method. The sampling of fish was carried out by the researchers and assisted by the people of the community using fishing rods and bubu fish traps. The results showed that 122 mudskipper were obtained, which consisted of four species Boleophthalmus boddarti, Boleophthalmus dussumieri, Periophthalmus chrysospilos, Periophthalmodon schlosseri. 93 male and 29 female fish were caught, the sex ratio was 3.20:1. There are more male than female fish overall with the sampling method used. Most of the female fish fecundity was reported in P. chrysospilos, namely 23,270-36,264 items in GM (III) and ranged from 40,825-87,749 items in GM (IV). The largest egg diameter was reported in P. chrysospilos by 0.051-0.069 mm (GML III) and 0.053-0.062 mm (GML IV), while the smallest weight and length were reported in P. chrysospilos than other species. The egg size was not positively correlated with body size.